GLYCEMIC CONTROL, HYPERTENSION AND CHRONIC COMPLICATIONS IN TYPE 2 DIABETIC SUBJECTS ATTENDING A TERTIARY CARE CENTRE - Basit, Abdul; Hydrie, Muhammad Zafar Iqbal; Hakeem, Rubina; Ahmedani, Mohammad Yakoob; Waseem, Mohiuddin (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to assess the association of glycemic control and hypertension with chronic complications in type 2 diabetic subjects attending a tertiary care centre in Karachi, Pakistan. Methods: This was a cross sectional analytical study. First visit of type 2 diabetic subjects to the outpatient department of Baqai Institute of Diabetology and Endocrinology, from September 1996 to December 2001, were analyzed for this study. Socio-demographic attributes and clinical profiles were obtained from the computerized records of these patients retrospectively. Odds ratio with 95% confidence interval were reported for independent variables associated with outcome variables. Results: Records of 2199 subjects (48.5% males, 51.5% females) were analyzed. Mean age of the male and female subjects was 52.2 and 50.6 years respectively. Hypertriglyceridemia [OR: 1.74; 95% CI (1.18-2.57)] and diabetic foot ulcers [OR: 2.32; 95% CI (1.14-4.01)] were significantly associated with poor glycemic control according to HbA1c. Whereas hypertriglyceridemia [OR: 2.39; 95% CI (1.42 -4.03)] and hypertension [OR: 1.65; 95% CI (1.13-2.41)] were significantly associated with poor glycemic control according to FPG. Obesity [OR: 1.44; 95% CI(1.18-1.75)], Retinopathy [OR: 1.95; 95% CI(1.49-2.53)], nephropathy [OR: 1.99; 95% CI(1.45-2.75)],neuropathy [OR:1.40; 95% CI(1.15-1.71)] and presence of coronary arterial disease [OR:1.33; 95% CI(1.02-1.72) were found to be significantly associated with systolic blood pressure. Obesity [OR:2.07; 95% CI(1.69-2.54)], hyperglycemia [OR: 1.40; 95% CI(1.04-1.90)] and nephropathy [OR: 1.92; 95% CI(1.39 -2.64)] had significant association with high diastolic blood pressure. Conclusion: In conclusion this study shows the association of chronic complications with glycemic control and hypertension amongst type 2 diabetics in Karachi. This information needs to be verified by multicentred large scale studies in order to be helpful in planning healthcare and treatment strategies. Keywords: diabetes, complications, microvascular, macrovascular, Pakistan, hypertension, glycemic control.